Development of Effective Liquid Fire-Extinguishing Compositions Based on Local Raw Materials - Erkinbaevich, Sabirov Erkaboy; Ergashevich, Kurbanbaev Shuxrat (European Journal of Life Safety and Stability (2660-9630), 2021)
the theoretical and practical foundations for ensuring fire safety by creating new liquid fire extinguishing compositions based on local raw materials.